2007
DOI: 10.1080/00016340701257141
|View full text |Cite
|
Sign up to set email alerts
|

Rupture of the scarred uterus

Abstract: In women with a scarred uterus, prostaglandin E2 induction of labour is a risk factor for uterine rupture. The practice of a systematic cesarean section in cases with Bishop score<3, appropriate induction procedure, and rigorous monitoring of the labour, could make for a safer delivery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 35 publications
0
13
1
1
Order By: Relevance
“…We further confirm risk factors such as abnormal placentation and increased maternal age as already described [22]. Induction of labor is postulated as important risk factor by many other authors, although this conclusion was not supported by all published studies [3,4,23,24]. In our study population, induction of labor in patients with previous uterine surgery seemed to be associated with uterine rupture (P < 0.01).…”
Section: Discussioncontrasting
confidence: 29%
“…We further confirm risk factors such as abnormal placentation and increased maternal age as already described [22]. Induction of labor is postulated as important risk factor by many other authors, although this conclusion was not supported by all published studies [3,4,23,24]. In our study population, induction of labor in patients with previous uterine surgery seemed to be associated with uterine rupture (P < 0.01).…”
Section: Discussioncontrasting
confidence: 29%
“…40 The impact of induction Induction of labour, especially with prostaglandins, increased the risk of uterine rupture in this sample as demonstrated elsewhere. 26,33,[41][42][43][44][45][46] Buhimschi et al 46 found that women induced with prostaglandins were more likely to rupture at the site of the uterine scar than those induced with oxytocin, suggesting that prostaglandins could induce local, biochemical modifications that weaken the scar, predisposing to rupture. Amniotomy and other mechanical methods carried lower risk of rupture than prostaglandin.…”
Section: 39mentioning
confidence: 99%
“…Controversy remains with respect to earlier stated additional risk of induction of labour with prostaglandins. Several studies report that induction with prostaglandins confers the highest risk of uterine rupture (relative risk up to 15), but two large studies could not confirm this 4,19,20 . Case ascertainment was suboptimal using ICD‐9 codes, and bias by indication may also have played a role.…”
Section: Discussionmentioning
confidence: 99%